1982
DOI: 10.1007/bf01675873
|View full text |Cite
|
Sign up to set email alerts
|

An orbital fistula complicating anaerobic frontal sinusitis and osteomyelitis

Abstract: Abstract. A patient is described with an orbital fistula complicating frontal sinusitis and osteomyelitis of the frontal bone. The fistula was excised, but a fortnight later an acute exacerbation occurred. From the discharging pus a Staphylococcus aureus was cultured and from mucosa obtained during surgery a microaerophilic Streptococcus. These findings led to the diagnosis: synergistic bacterial inflammation of the frontal sinus, with osteomyelitis and orbital cellulitis. Case reportA 20-year-old soldier visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…2 In 2008, Wu et al 3 reported 13 cases from the English literature published since 1950 with SCF as a complication of frontal sinusitis, 4 of which also had associated PPT (Table 1). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Simonin et al's 4 literature review after 2008 described 5 more cases of SCF and PPT as complications of chronic sinusitis and 1 case with post-traumatic right frontal craniotomy and cranial osteoplastic reconstructive surgery. There were only 3 reported cases of ECF associated with PPT as a complication of frontal sinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…2 In 2008, Wu et al 3 reported 13 cases from the English literature published since 1950 with SCF as a complication of frontal sinusitis, 4 of which also had associated PPT (Table 1). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Simonin et al's 4 literature review after 2008 described 5 more cases of SCF and PPT as complications of chronic sinusitis and 1 case with post-traumatic right frontal craniotomy and cranial osteoplastic reconstructive surgery. There were only 3 reported cases of ECF associated with PPT as a complication of frontal sinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…The range of potential pathogens is remarkably wide, 17 –21 and commonly identified bacteria include aerobic and anaerobic streptococci, staphylococci and bacteroides species 2 , 5 . The low incidence of haemophilus, particularly in adults, 5 may reflect widespread use of the H. influenzae type B vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic orbital osteomyelitis is rare, with only scattered case reports available [3,4,5,6,7,8,9,10]. These reported that chronic orbital osteomyelitis was almost secondary to sinusitis or trauma accompanying retained foreign bodies.…”
Section: Discussionmentioning
confidence: 99%